Determination of Collagen Fibers Arrangement in Bone Tissue by Using Transformations of Raman Spectra Maps. Issue 2 (28th May 2012) - Buchwald Buchwald, Tomasz Tomasz; Kozielski Kozielski, Marek Marek; Szybowicz Szybowicz, Mirosław Mirosław
Abstract : The goal of this work was to evaluate the ability of Raman spectroscopy to identify molecular organization and chemical composition of extracellular matrix such as the collagen fibers arrangement, the level of mineralization, and the carbonate accumulation in mineral phase in spongy bone of the human head of the femur. Changes in composition and structure of the spongy bone tissue were illustrated using maps of polarized Raman spectra. In particular, the purpose of the present study was determination of arrangement of mineralized collagen on surface of trabecula by using transformations of Raman spectra maps. Transformations of Raman spectra maps were needed in order to remove impact of chemical composition on images of Raman spectra map, which display the collagen fibers orientation. These transformations allow to obtain simultaneously the distribution of constituents of bone and arrangement of collagen fibers on tissue surface. A method to indicate the collagen orientations is developed to understand the molecular organization in healthy and unhealthy bone at the microstructural level.